Implementation of the PHBS (Clean and Healthy Living Behaviour) Program in Preventing Communicable Diseases in the Environment of Elementary School 11 Lubuk Buaya Padang - Yoanita Hijriyati; Titis Istiqomah; Hilda Harun; Mila Sari; Wedia Hastuti (CV. Get Press Indonesia, 2025)
The implementation of the Clean and Healthy Living Behaviour (PHBS) programme in the elementary school environment constitutes a significant preventive measure in the reduction of the incidence of infectious diseases. The present research employs a descriptive qualitative approach through a participatory-based community service method that focuses on the implementation and evaluation of the effectiveness of the PHBS Program in preventing infectious diseases in the primary school environment. The target audience comprised 30 students in grades IV to VI, three homeroom teachers, and School Health Unit (UKS) administrators, all of whom participated in every stage of the activity. The qualitative data was analysed descriptively by comparing pretest and posttest scores, while qualitative data were analysed using data reduction techniques, thematic categorisation and narrative interpretation to obtain a more holistic picture of changes in students' knowledge, attitudes, behaviour, and collective awareness of the importance of healthy living. The programme has been demonstrated to be effective in the transformation of theoretical understanding into concrete habits within the school environment through the implementation of interactive, visual-based, and hands-on educational approaches, including role play and simulation. Its success has been demonstrated as a preventative strategy against infectious diseases, as well as an effective character-building approach for students in maintaining hygiene and health independently and sustainably.